Love in black and white : a memoir of race, religion, and romance - Cohen, William S. (Rowman & Littlefield Publishers : Distributed by National Book Network, 2007)
In a world where it was commonplace to see signs that read "whites only" or "Jews not allowed," William Cohen was born in Bangor, Maine, the eldest son of a Jewish father and a Protestant Irish mother. Janet Langhart, an African-American, was raised in Indianapolis, Indiana by her single parent mother, a Southern Baptist. These two people, from different regions, races, and religions, are both witnesses to and targets of the social tensions of the day. Their stories are rich and profound; at times they are amusing, at others harrowing. Bill would be elected to serve his country as a U.S. Congressman and Senator, and Janet would become a prominent television personality, activist, and highly respected businesswoman and author. Opposites in so many ways--in color, faith and culture--seemingly a bundle of contradictions, they meet in 1974, become friends, and eventually marry in 1996, in the U.S. Capitol.--From publisher description.